Pendampingan Masyarakat dalam Upaya Pengembangan Daya Tarik Wisata Alam dan Budaya Kasepuhan Ciptagelar - Hari Muharam; Hari Gursida; Ramon Hurdawaty; Yandi Asmana; Hammad Hammad; Endi Suyatno (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
The Kasepuhan Cipta Gelar traditional village is in Sukabumi Regency, West Java. The majority of the village population lives from rice cultivation, and the village is very attached to the culture of their ancestors. The combination of cultural and natural aspects offers an experience to tourists. Tourism development that combines these two aspects allows the creation of sustainable and responsible tourism products, which not only increase economic value but also preserve and respect cultural heritage and natural sustainability. Community service activities carried out aim to provide input to traditional stakeholders and the Kasepuhan Ciptagelar community in identifying and analyzing potential tourist attractions from a cultural and natural perspective and strategies for developing tourist attractions. Community service activities in the form of community assistance were carried out on December 17, 2023. The results included identifying natural and cultural tourist attractions in Kasepuhan Ciptagelar and providing information about tourism potential, tourism management, and tourism marketing as input to traditional stakeholders and local communities.